Exploring theophylline-1,2,4-triazole tethered N-phenylacetamide derivatives as antimicrobial agents: unraveling mechanisms via structure-activity relationship, in vitro validation, and in silico insights - Saeed, Sadaf; Shahzadi, Irum; Zahoor, Ameer Fawad; Al-Mutairi, Aamal A.; Kamal, Shagufta; Faisal, Shah; Irfan, Ali; Al-Hussain, Sami A.; Muhammed, Muhammed Tilahun; Zaki, Magdi E. A. (Frontiers in Chemistry, 2024)
Theophylline, a nitrogen-containing heterocycle, serves as a promising focal point for medicinal researchers aiming to create derivatives with diverse pharmacological applications. In this work, we present an improved synthetic method for a range of theophylline-1,2,4-triazole-S-linked N-phenyl acetamides (4a‒g) utilizing ultrasound-assisted synthetic approach. The objective was to assess the effectiveness of synthesized theophylline-1,2,4-triazoles (4a‒g) as inhibitors of HCV serine protease and as antibacterial agents against B. subtilis QB-928 and E. coli AB-274. Theophylline-1,2,4-triazoles were obtained in good to excellent yields (69%–95%) in a shorter time than conventional approach. 4-Chlorophenyl moiety containing theophylline-1,2,4-triazole 4c displayed significantly higher inhibitory activity against HCV serine protease enzyme (IC50 = 0.015 ± 0.25 mg) in comparison to ribavirin (IC50 = 0.165 ± 0.053 mg), but showed excellent binding affinity (−7.55 kcal/mol) with the active site of serine protease, better than compound 4c (−6.90 kcal/mol) as well as indole-based control compound 5 (−7.42 kcal/mol). In terms of percentage inhibition of serine protease, 2-chlorophenyl compound 4b showed the maximum percentage inhibition (86%), more than that of the 3,4-dichlorophenyl compound 4c (76%) and ribavirin (81%). 3,4-Dimethylphenyl-based theophylline-1,2,4-triazole 4g showed the lowest minimum inhibitory concentration (MIC = 0.28 ± 0.50 μg/mL) against the B. subtilis bacterial strain as compared to the standard drug penicillin (MIC = 1 ± 1.50 μg/mL). The other 4-methylphenyl theophylline-1,2,4-triazole 4e (MIC = 0.20 ± 0.08 μg/mL) displayed the most potent antibacterial potential against E. coli in comparison to the standard drug penicillin (MIC = 2.4 ± 1.00 μg/mL). Molecular docking studies further helped in an extensive understanding of all of the interactions between compounds and the enzyme active site, and DFT studies were also employed to gain insights into the molecular structure of the synthesized compounds. The results indicated that theophylline-linked triazole derivatives 4b and 4c showed promise as leading contenders in the fight against the HCV virus. Moreover, compounds 4e and 4g demonstrated potential as effective chemotherapeutic agents against E. coli and B. subtilis, respectively. To substantiate these findings, additional in vivo studies and clinical trials are imperative, laying the groundwork for their integration into future drug design and development.